2001
DOI: 10.1080/j.1600-0412.2001.080006546.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-binding protein-1 in cervical secretion as a predictor of preterm delivery

Abstract: Pregnant women who are in preterm labor with intact fetal membranes and who have a positive phIGFBP-1 test result in cervical secretion have an increased risk of preterm delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 0 publications
1
40
1
2
Order By: Relevance
“…In a study by the expression of IGF-I and IGFBP-1 gene in the placenta decreases from 35-37 weeks to 38-40 weeks [47]. In pregnancies complicated with preterm delivery decreased levels of IGFBP-1 in placental extracts [48] increased levels of IGFBP-1 in cervical secretion, and the amniotic fluid [49][50][51] and decreased IGFBP-3 concentrations in the maternal circulation [52] have been found. This may reflect changes in the placental expression of these genes, which, however, has not yet been investigated.…”
Section: Discussionmentioning
confidence: 93%
“…In a study by the expression of IGF-I and IGFBP-1 gene in the placenta decreases from 35-37 weeks to 38-40 weeks [47]. In pregnancies complicated with preterm delivery decreased levels of IGFBP-1 in placental extracts [48] increased levels of IGFBP-1 in cervical secretion, and the amniotic fluid [49][50][51] and decreased IGFBP-3 concentrations in the maternal circulation [52] have been found. This may reflect changes in the placental expression of these genes, which, however, has not yet been investigated.…”
Section: Discussionmentioning
confidence: 93%
“…The same conclusion was reached by another group [16] who tested the reliability of the Actim Partus test in predicting preterm deliveries. Kekki et al [17] also discussed the high negative predictive value of determining IGFBP-1, and Bittar [18] also tested pregnant women without symptoms of preterm delivery and found that the sensitivity of the test was 83%, positive predictive value 63%, specificity 80%, and negative predictive value 92%. Similar results of high specificity and negative predictive value in asymptomatic pregnant women were shown in other studies published last year [19,20,21,22].…”
Section: Discussionmentioning
confidence: 98%
“…IGFBP-1 and phIGFBP-1 can be differentiated by the use of unique antibodies [135]. Consequently, the presence of IGFBP-1 can be used to detect PROM and the presence of phIGFBP-1 to predict preterm labor [136,137]. In addition, measurement of phIGFBP-1 from cervical secretions can also be used to estimate the ripeness of the cervix [138].…”
Section: Insulin-like Growth Factor Binding Proteins (Igfbp)mentioning
confidence: 99%